2005
DOI: 10.1073/pnas.0508085102
|View full text |Cite
|
Sign up to set email alerts
|

Intronic regulation of matrix metalloproteinase-2 revealed by in vivo transcriptional analysis in ischemia

Abstract: Matrix metalloproteinase-2 (MMP-2) plays an essential role in angiogenesis and arteriogenesis, two processes critical to restoration of tissue perfusion after ischemia. MMP-2 expression is increased in tissue ischemia, but the responsible mechanisms remain unknown. We studied the transcriptional activation of the MMP-2 gene in a model of hindlimb ischemia by using various MMP-2-lacZ reporter mice and chromatin immunoprecipitation. MMP-2 activity and mRNA were increased after hindlimb ischemia. Mice with target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 42 publications
1
38
1
1
Order By: Relevance
“…Sequence analysis of the promoter/enhancer region shows potential binding sites for multiple transcription factors including AP-1, RE-1, Ets-1, Sp-1, and AP-2. Previous work showed that the family of AP-1 transcription factors are involved in upregulation of MMP-2 activity in cardiac 19 and skeletal muscle 20 and in other types of muscle dysfunction, such as those associated with ischemia-reperfusion injury. We found a significant increase in expression of FosB and c-Jun, two members of the AP-1 family, in the atrophic muscle compared to the control.…”
Section: Discussionmentioning
confidence: 99%
“…Sequence analysis of the promoter/enhancer region shows potential binding sites for multiple transcription factors including AP-1, RE-1, Ets-1, Sp-1, and AP-2. Previous work showed that the family of AP-1 transcription factors are involved in upregulation of MMP-2 activity in cardiac 19 and skeletal muscle 20 and in other types of muscle dysfunction, such as those associated with ischemia-reperfusion injury. We found a significant increase in expression of FosB and c-Jun, two members of the AP-1 family, in the atrophic muscle compared to the control.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, the full-length promoter region for MMP-2 or MMP-9 fused to a reporter has been permanently ligated into the murine system (4,220,286). With the use of this approach, MMP transcriptional activity can be quantified as well as localized.…”
Section: Myocardial Restricted Overexpression/gene Transfer Studiesmentioning
confidence: 99%
“…The full-length human MMP-2 or MMP-9 promoter was ligated to the ␤-galactosidase reporter and fused into mice (4,220,286). This approach provides for spatial localization of MMP-2 and MMP-9 promoter activity.…”
Section: Gene Polymorphism Observationsmentioning
confidence: 99%
“…Ischemia induced the expression and binding of c-Fos, c-Jun, JunB, FosB, and Fra2 to a noncanonical AP-1 site present in the MMP-2 promoter and decreased binding of the transcriptional repressor JunD. In a model of hind limb ischemia, the MMP-2 promoter was also enhanced by increased expression and binding of nuclear factor of activated T-cells-c2 (NFATc2) to consensus sequences within the first intron (67). In this model, deletion of either the 5Ј regulatory element (RE) region of the promoter or substitution of the first intron abolished ischemia-induced MMP-2 transcription in vivo.…”
Section: Volume 287 • Number 48 • November 23 2012mentioning
confidence: 99%